Treating Hypertension in Pregnancy. Issue 4 (21st December 2022) - Greene, M.; Williams, W.
Abstract : ( N Engl J Med . 2022;386:1846–1847. doi: 10.1056/NEJMe2203388) Chronic hypertension impacts 2.2% of 3.7 million births in 2019 in the United States, and this number continues to grow, likely due to the increasing rate (55.9% of all pregnancies in 2019) of obesity in pregnancy and the number of pregnancies occurring after the maternal age of 35. Impacts of maternal hypertension include preeclampsia, eclampsia, stroke, heart failure, pulmonary edema, acute kidney injury, placental abruption, increased risk of preterm birth, failed fetal growth, perinatal death, and maternal death. Unfortunately, Black women are specifically affected. In an effort to combat this, medication and other medical treatment are given to those women suffering from severe chronic hypertension. However, small original studies examining the impact of hypertension treatment on those with less severe or mild chronic hypertension did not demonstrate improvement. In fact, the fetus was possibly negatively impacted.